2019
DOI: 10.1111/jpn.13211
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related intestinal monosaccharides transporters expression and villus surface area increase in broiler and layer chickens

Abstract: In the chicken small intestine, glucose is mainly transported by the apically located sodium/glucose cotransporter 1 (SGLT1) and the basolaterally located glucose transporter 2 (GLUT2). Fructose is transported by the apically located glucose transporter 5 (GLUT5) and similarly by GLUT2. During the early post‐hatching period, the intestinal villus surface area (VSA) should be considered as an important factor related to the monosaccharide absorption capacity. Our objective here was to study intestinal monosacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Further and as was previously suggested, these functional changes, as demonstrated via gene expression of key BBM proteins (zinc transporter, inflammatory cytokines, absorptive proteins, and mucin), were previously associated with BBM tissue physiological and morphometric alterations, as increased villi size [ 24 , 50 , 93 , 94 , 95 , 96 , 97 ]. These alterations may potentially also be associated with increased proliferation of cellular populations that hold essential roles in BBM function, including, enterocytes, and therefore, increased villus surface area (the intestinal digestive and absorptive surface), and goblet cells (produce and secrete mucus), both number and diameter in intestinal villi and crypt [ 18 , 22 , 24 , 47 , 50 , 93 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. In this context, it was previously demonstrated that colonocytes and enterocytes oxidation pathways utilize butyrate as fuel for cell metabolism [ 106 , 107 , 108 ], via SL16 monocarboxylate transporter 1 (MCT1, SCL16A1) and Sodium-coupled monocarboxylate transporter 1 (SMCT1, SLC5A8) that transport butyrate through epithelial cells in the small intestine [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further and as was previously suggested, these functional changes, as demonstrated via gene expression of key BBM proteins (zinc transporter, inflammatory cytokines, absorptive proteins, and mucin), were previously associated with BBM tissue physiological and morphometric alterations, as increased villi size [ 24 , 50 , 93 , 94 , 95 , 96 , 97 ]. These alterations may potentially also be associated with increased proliferation of cellular populations that hold essential roles in BBM function, including, enterocytes, and therefore, increased villus surface area (the intestinal digestive and absorptive surface), and goblet cells (produce and secrete mucus), both number and diameter in intestinal villi and crypt [ 18 , 22 , 24 , 47 , 50 , 93 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. In this context, it was previously demonstrated that colonocytes and enterocytes oxidation pathways utilize butyrate as fuel for cell metabolism [ 106 , 107 , 108 ], via SL16 monocarboxylate transporter 1 (MCT1, SCL16A1) and Sodium-coupled monocarboxylate transporter 1 (SMCT1, SLC5A8) that transport butyrate through epithelial cells in the small intestine [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was not surprising that no response to mucosal glucose addition could be detected in cecal tissues. Though there are limited studies on glucose transport in turkey intestines, in chickens, glucose is not only absorbed via SGLT1 but also the non-electrogenic apical and basolateral glucose transporters GLUT5 and GLUT2, respectively [ 34 , 35 ]. Further, glucose transporters seem to be downregulated significantly after seven to 28 days of life when the main growth period is over [ 34 ], which may also be the case in turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are limited studies on glucose transport in turkey intestines, in chickens, glucose is not only absorbed via SGLT1 but also the non-electrogenic apical and basolateral glucose transporters GLUT5 and GLUT2, respectively [ 34 , 35 ]. Further, glucose transporters seem to be downregulated significantly after seven to 28 days of life when the main growth period is over [ 34 ], which may also be the case in turkeys. Nevertheless, studies in chickens also showed that C. jejuni- inoculation caused a downregulation of both SGLT1 and GLUT2 gene expression [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be further noted that fasting slightly decreased the total tract digestibility of total starch in broilers. The lower total tract digestibility of total starch in broilers than adult roosters in this study may be explained by the lower monosaccharide transporter expression in broilers compared to adult roosters ( Li et al., 2020 ). Similarly, decreased total tract digestibility of total starch was found in 20-day-old broilers that fasted for 16 h ( Peron et al., 2005 ).…”
Section: Discussionmentioning
confidence: 65%
“…More recently, researchers have found that fasting influences the development of the small intestine ( Lu et al., 2020 ; Yang et al., 2020 ), thereof the absorptive functions. Development of digestive and absorptive functions in adult roosters is different from that of broilers ( Lilburn and Loeffler, 2015 ; Fondevila et al., 2020 ), in terms of intestinal nutrient transporters expression, villus surface area ( Li et al., 2020 ) and relative weight of digestive organs ( Yang et al., 2020 ). Correspondingly, it has indicated that apparent metabolizable energy ( AME ), TME, and nutrient digestibility varied with age of birds ( Dale and Fuller, 1980 ; Stefanello et al., 2016 ; Yang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%